Assessment of Dissolution Profile of Aceclofenac Tablets Available in Bangladesh - Ahmed, Tajnin; Ferdous, Afia; Biswas, Subrata Kumar; Sharif, Farhana (Stamford Journal of Pharmaceutical Sciences, 2011)
The objective of this work is to find out brand-to-brand variation by applying profile comparison approaches to the dissolution data of marketed aceclofenac tablet formulations. Commercially available five brands of aceclofenac tablets were studied in simulated intestinal medium (pH 6.8) for 60 minutes time period using USP reference dissolution apparatus. Four samples complied with the USP in vitro dissolution specifications for drug release (not less than 80% of the labeled amount of Aceclofenac should be dissolved in 60 minutes). One brand (Code: S1) failed to meet the criteria; drug release was 66.85% within the specified time period. Key words: Bangladesh; In vitro dissolution; market preparations; aceclofenac; tablet. DOI: 10.3329/sjps.v3i1.6790 S. J. Pharm. Sci. 3(1): 1-3